Medição da velocidade do som no ar com o uso de Arduino - Lopes, José Ivo de Jesus Silva (Universidade Federal Rural do Semi-Árido, 2019)
Using free technologies to eliminate the cost of purchasing paid software, a prototype was produced that has the ability to measure the speed of sound in the air with the help of Arduino, an easy-to-use tool, as there is a community that uses and shares the necessary codes and schemas. The system was designed using Arduino board, protoboard board, Ultrasonic Sensor, Liquid Crystal Display (LCD), Potentiometer, Jumpers and IDE (Integrated Development Environment). All of these devices act simultaneously to achieve the desired results, each with its own specific function for the best prototype performance. The idea is to facilitate the teaching of physics with the use of practical and low cost experiments, aiming at the implementation of this practice in teaching-learning. The results were consistent with the values found in the literature, thus concluding that the prototype achieved its objectives.
Keywords: Velocidade do som; Arduino; Ultrassônico; Protótipo; Speed of sound; Arduino; Ultrasonic; Prototype; CIENCIAS EXATAS E DA TERRA::CIENCIA E TECNOLOGIA